Shadowed Dreams : Women's Poetry of the Harlem Renaissance - Honey, Maureen, 1945- (Book collections on Project MUSE., 2006)
The first edition of Shadowed Dreams was a groundbreaking anthology that brought to light the contributions of women poets to the Harlem Renaissance. This revised and expanded version contains twice the number of poems found in the original, many of them never before reprinted, and adds eighteen new voices to the collection to once again strike new ground in African American literary history. Also new to this edition are nine period illustrations and updated biographical introductions for each poet. Shadowed Dreams features new poems by Gwendolyn Bennett, Anita Scott Coleman, Mae Cowdery, Blanche Taylor Dickinson, Alice Dunbar-Nelson, Jessie Fauset, Angelina Weld Grimke, Gladys Casely Hayford (a k a Aquah Laluah), Virginia Houston, Georgia Douglas Johnson, Helene Johnson, Effie Lee Newsome, Esther Popel, and Anne Spencer, as well as writings from newly discovered poets Carrie Williams Clifford, Edythe Mae Gordon, Alvira Hazzard, Gertrude Parthenia McBrown, Beatrice Murphy, Lucia Mae Pitts, Grace Vera Postles, Ida Rowland, and Lucy Mae Turner, among others. Covering the years 1918 through 1939 and ranging across the period's major and minor journals, as well as its anthologies and collections, Shadowed Dreams provides a treasure trove of poetry from which to mine deeply buried jewels of black female visions in the early twentieth century.